Development of Promoting Morale Model in Teacher Performance Under the Secondary Educational Service Area Office Ratchaburi - Kongkasai, Kanthika; Intarak, Choomsak; Natthunatiruj, Rhoamrumpha (Journal of Graduate MCU KhonKaen Campus, 2025)
The purposes of this research and development were to 1) Study the problem of enhancing teachers’ morale in their work performance. 2) Design and create a model for enhancing teachers’ morale in their work performance. 3) Evaluate the model for enhancing teachers’ morale in their work performance. 4) Compare the results of the experiment of the model for enhancing the morale of teachers in their work performance and 5) Study the results of using the model to enhance morale in the work of teachers under the Office of the Secondary Education Area, Ratchaburi, in terms of efficiency, effectiveness and value. The population comprised 26 schools under the Secondary Educational Service Area Office Ratchaburi, with 3 respondents from each school; the principal, the vice principal or head of human resource management, and a teacher, totaling 78 respondents. The experiment was conducted at Queen College School. The research instruments included questionnaires, model evaluation forms, pre - and post-test evaluations, and efficiency, effectiveness, and value assessments. The reliability of the instruments was confirmed using content validity, with an Index of Consistency (IOC). Data were analyzed using frequency, percentage, arithmetic mean, standard deviation, content analysis, and dependent t-tests. The research findings revealed that: 1) the problems concerning morale promotion in teacher performance were reported at a high level. 2) the constructed model, composed of success goal setting, policy making, responsibility, relationship, and environment named the GP-3RE Model. 3) The evaluation of the model yielded an IOC value ranging from 0.80 to 1.00 4) A comparison of pre-and post-test results demonstrated a statistically significant improvement at the .01 level. 5) The model was rated the highest levels in effectiveness, efficiency, and value. It is recommended that school administrators should adopt this model to promote teacher morale and improve both the efficiency and effectiveness of their work performance.